Bank ownership structure, regulations and risk-taking : evidence from commercial banks in Pakistan - Ehsan, Sobia (2018)
This paper conducts the first empirical assessment of the theories concerning the influence of ownership structure on bank risk-taking in the presence of regulations in Pakistan. The sample used in this paper comprises a panel data of 26 banks in Pakistan, for the period from 2000 to 2014. The analysis provides evidence that increase in ownership concentration leads to an increase in bank risk-taking. Managerial ownership is associated with high risk-taking at low and high levels of managerial ownership while at intermediate level, managerial ownership has negative impact on bank risk-taking. Different types of ownership of banks in Pakistan have different impact on risk-taking. While government, family and institutional ownership have a positive impact on bank risk-taking, foreign own- ership has a negative impact on bank risk-taking. Furthermore, the results show that capital regulations are important in influencing bank risk-taking with regard to higher ownership concentration. The findings of this paper suggest that the relation between bank risk-taking and capital regulations typically depends on the type of ownership.